GAMBARAN TINGKAT PENGETAHUAN PERAWATAN DENTAL BLEACHING PADA PETUGAS TELLER DAN CUSTOMER SERVICE BANK DI KOTA PADANG - Deli Mona; Rinang Mariko; Dina Wardaningsih (Universitas Fort De Kock, 2022)
Dental bleaching is an aesthetic dental care that popular in the society. Public interest in the dental bleaching increase as the increasing the need of aesthetic itself, especially in those who work as teller and customer service who always interacts with people and need to look good. Dental bleaching uses chemical material which has side effects for the consumer, if it is being used freely without awareness about its procedures and a dentist’s supervision. The aim of study is to know the description about teller and customer service knowledge on dental bleaching. This study uses descriptive method. The sample of study is 65 tellers and customer services of BNI, Nagari, CIMB Niaga, Bukopin, Kesejahteraan, Maybank, and Pundi in Padang. The sampling technique is probability proportional to size. There are 26 (40%) respondent had high level knowledge about dental bleaching and 39 (60%) respondent had low level knowledge about dental bleaching. The conclusion of this study is most of the tellers and customer services had low level knowledge about dental bleaching care, that is 39 (60%) respondent.